2011
DOI: 10.3171/2010.9.jns10816
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife surgery for subependymal giant cell astrocytomas

Abstract: Object. The authors report their experience of using Gamma Knife surgery (GKS) in patients with subependymal giant cell astrocytoma (SEGA).Methods. Over a 20-year period, the authors identified 6 patients with SEGAs who were eligible for GKS. The median patient age was 16.5 years (range 7-55 years). In 4 patients, GKS was used as a primary management therapy. One patient underwent radiosurgery for recurrent tumors after prior resection, and in 1 patient GKS was used as an adjunct after subtotal resection. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 26 publications
0
20
1
Order By: Relevance
“…Overall, this rate compares similarly with rates seen after radiosurgery or everolimus alone. 13,17 No complications were noted during these treatments. While no tumor was completely extirpated after laser ablation, there were marked reductions in tumor volumes up to 70%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, this rate compares similarly with rates seen after radiosurgery or everolimus alone. 13,17 No complications were noted during these treatments. While no tumor was completely extirpated after laser ablation, there were marked reductions in tumor volumes up to 70%.…”
Section: Discussionmentioning
confidence: 99%
“…However, in incompletely resected SEGAs, up to 100% reoperation rates are noted. 1 Radiosurgery has also been used for inoperable tumors with reported long-term control rates of 67%, 17 and recent introduction of everolimus, an mTOR inhibitor, has provided new options for medical management. 13 Again, there exists a potential role for laser ablation for management of inoperable, symptomatic SEGAs, especially with its potential to reduce tumor volume and improve associated mass effect and/or CSF outlet obstruction.…”
mentioning
confidence: 99%
“…GKR revealed good outcomes for many types of benign brain tumors, including gliomas, with a low incidence of side effects [22]. Out of reported cases of SEGA after GKR, half of them showed tumor volume reduction 70–80% within 6 months, and another shown tumor progression [22232425]. Even though the role of GKR in SEGAs was limited by the sporadic cases, these reported results suggest GKR may be an additional option for SEGAs that are small but progressively enlarging tumors where complete resection has not been safely achieved, residual or recurrent tumors.…”
Section: Discussionmentioning
confidence: 99%
“…An additional study that included two patients with SEGAs observed a radiographic response in one patient and progression in the other after a median dose of 13 Gy [18]. More recently, a study of six TSC patients with SEGA who received a median dose of 14 Gy reported local tumor control in four patients with progression-free intervals of 24, 42, 57, and 66 months [19]. Importantly, "tumor control" was defined as <25 % increase in enhancing or nonenhancing tumor volume, whereas "tumor progression" was defined as ≥25 % increase in tumor volume.…”
Section: Gamma Knife Stereotactic Radiosurgerymentioning
confidence: 93%